Firearm assault in Philadelphia, 2005–2014: a comparison of police and trauma registry data. Issue 1 (12th August 2019) - Kaufman, Elinore; Holena, Daniel N; Yang, Wei P; Morrison, Christopher N; Jacoby, Sara F; Seamon, Mark; Sims, Carrie; Wiebe, Douglas J; Beard, Jessica H
Abstract : Background: Firearm injury is a major public health burden in the USA. Absent a single, reliable data source, researchers have attempted to describe firearm injury epidemiology using trauma registry data. To understand the implications of this approach, we compared trends in firearm assault incidence and case-fatality in Philadelphia over 10 years from two sources: the Pennsylvania Trauma Outcomes Study (PTOS), Pennsylvania's state-mandated trauma registry, and the Philadelphia Police Department database (PPD) of firearm assaults. Methods: We included PTOS firearm assault patients treated in Philadelphia County and PPD database firearm assault victims from 2005 to 2014. We calculated counts of fatal and non-fatal incidents using PTOS and PPD data. We used generalized linear models adjusted for seasonality to estimate temporal trends in firearm assault rates and case-fatality for both data sources and compared patient demographics and injury characteristics between the two. Results: A total of 6988 PTOS and 14 172 PPD subjects met the inclusion criteria. In both data sets, firearm assault rates decreased significantly during the study period (PTOS: 5.19 vs. 3.43 per 10 000 person-years, change/year: −0.21, 95% CI −0.26 to –0.16; PPD: 10.97 vs. 6.70 per 10 000 person-years, change/year: −0.53, 95% CI −0.62 to –0.44). PTOS mean case-fatality rate was 26.5% and decreased significantly (change/year: −0.41, 95% CI −0.78% to 0.04%). PPD mean case-fatality rate was 18.9% with no significant change over time (p=0.41). Discussion: Relative to PPD data, PTOS data underestimated firearm assault incidence and overestimated mortality. Trends in case-fatality rates were disparate across the two data sources. A true understanding of firearm injury in the USA requires comprehensive data collection on the incidence, nature, and severity of these injuries. As trauma registry data are by definition incomplete, combining data sources is essential. Local law enforcement data are an important potential source for studying city-level firearm injury. Level of evidence: Level III, epidemiological.